2010
DOI: 10.1038/npre.2010.4995.1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical nanomechanics of collagen microfibrils

Abstract: Collagen constitutes one third of the human proteome, providing mechanical stability, elasticity and strength to connective tissues. Collagen is also the dominating material in the extracellular matrix (ECM) and is thus crucial for cell differentiation, growth and pathology. However, fundamental questions remain with respect to the origin of the unique mechanical properties of collagenous tissues, and in particular its stiffness, extensibility and nonlinear mechanical response. By using x-ray diffraction data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This specific structure results in remarkable compression and bending resistance, greatly enhancing the bone's overall mechanical properties. 20,53–55…”
Section: Types Of Bionic Ordered Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific structure results in remarkable compression and bending resistance, greatly enhancing the bone's overall mechanical properties. 20,53–55…”
Section: Types Of Bionic Ordered Structuresmentioning
confidence: 99%
“…This specific structure results in remarkable compression and bending resistance, greatly enhancing the bone's overall mechanical properties. 20,[53][54][55] The prevalence of ordered lamellar structures in organisms provides researchers with opportunities to enhance the mechanical properties of hydrogels by imitating such structures. Bionic lamellar structure hydrogels are generally fabricated by stacking nanosheets to form a lamellar structure.…”
Section: Lamellar Structuresmentioning
confidence: 99%
“…In particular, hierarchical microstructures are ubiquitous in biomaterials [3]. An example is the hierarchical modular organization of collagen, ranging from molecules over microfibrils and fibers to hierarchical fiber bundles, ensuring enhanced toughness of the hierarchical structure over that of an assembly of isolated collagen molecules [4]. Other examples include the hierarchical structure of bone [5,6], the cellular structure of wood [3], or the hierarchical lamellar microstructure of tortoise shells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials such as the spider silk and bones are usually super strong to withstand the huge and dynamic loads coming from the surrounding environment. Studies have shown that these biomaterials can achieve energy dissipation at the molecular scale by exploiting the sacrificial bond destruction and hidden length release at the soft‐hard interfaces, hence the excellent physical and mechanical performance of biomaterials are achieved . Inspired by the structure of natural biomaterials, researchers have used appropriate strategies at the elastomer‐filler interfaces to construct the sacrificial bonds and hidden length, which is similar to natural biomaterials, in order to obtain both strength and toughness of composites in recent years.…”
Section: Introductionmentioning
confidence: 99%